Correlation between Obesity and Pregnancy Outcomes, Miscarriage, and Mode of Delivery - Nurinasari, Hafi; Fathimatuzzahrah, Hanifah; Pradipta, Ghazy Wira; Octaviany, Frisca Fadhilah; Anggraeni, Asih; -, Soetrisno (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: The obesity pandemic is a source of problems in both developed countries. The obesity is associated with complications before and during pregnancy and even infant death. The study aims to find out the issue of obesity among women of reproductive age, particularly concerning its impact on maternal and fetal outcomes during pregnancy.Methods: This is a cross-sectional observational study using secondary data with medical records taken at Sebelas Maret University Hospital (UNS Hospital). Subjects were obese pregnant women who gave birth at UNS Hospital. Data from 284 single births were added maternal parameters, obstetric parameters, and newborn parameters were taken and then analyzed univariately, and bivariate analysis was carried out using the Kruskall-Wallis test and the Spearman test for comparison and correlation of each variable.Results: This study finds lower incidences of postdate pregnancy and instrumental deliveries among obese mothers, but a higher rate of emergency cesarean sections. Newborn anthropometric measurements increase with maternal BMI, indicating a direct association between maternal obesity and newborn health (p = 0.001), while APGAR scores show no significant differences among maternal BMI groups. The findings underscore the importance of addressing maternal obesity to improve both maternal and newborn health outcomes.Conclusion: The research indicates a correlation between maternal BMI, maternal obstetric characteristics, newborn anthropometric measurements, and APGAR scores. This suggests that interventions aimed at promoting healthy maternal BMI, beginning before conception, continuing throughout pregnancy, and extending into the post-pregnancy period, could potentially improve newborn health outcomes and give long-term health benefits.